2022
DOI: 10.3389/fmicb.2022.877990
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal Capacity of Microbial Communities Developing in Compost- and Woodchip-Based Multipurpose Reactive Barriers for Aquifer Recharge With Wastewater

Abstract: Global water supplies are threatened by climate changes and the expansion of urban areas, which have led to an increasing interest in nature-based solutions for water reuse and reclamation. Reclaimed water is a possible resource for recharging aquifers, and the addition of an organic reactive barrier has been proposed to improve the removal of pollutants. There has been a large focus on organic pollutants, but less is known about multifunctional barriers, that is, how barriers also remove nutrients that threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
(63 reference statements)
2
6
0
Order By: Relevance
“…That is, the presence of the reactive barrier enhanced the biological activity and the organic carbon oxidation, which is consistent with observations of Valhondo et al ,, Recall that the reactive barrier had been installed 2 years before the slug injection, and one of its goals was to release DOC to favor reducing conditions. By the end of this 2-year period, it was expected that this release had been largely depleted. , Therefore, we attribute the higher degradation in the CT system to a richer bacterial activity as was established in Hellman et al The greater reactivity in CT is also supported by the Li + breakthrough curves (Figure S2). The tail of Li + lasts longer than that of CE, and more so for the CT, while the peak arrivals are similar, which reflects both that Li + is adsorbed and that adsorption is noninstantaneous (otherwise the Li + peak arrival would have been retarded).…”
Section: Resultssupporting
confidence: 62%
“…That is, the presence of the reactive barrier enhanced the biological activity and the organic carbon oxidation, which is consistent with observations of Valhondo et al ,, Recall that the reactive barrier had been installed 2 years before the slug injection, and one of its goals was to release DOC to favor reducing conditions. By the end of this 2-year period, it was expected that this release had been largely depleted. , Therefore, we attribute the higher degradation in the CT system to a richer bacterial activity as was established in Hellman et al The greater reactivity in CT is also supported by the Li + breakthrough curves (Figure S2). The tail of Li + lasts longer than that of CE, and more so for the CT, while the peak arrivals are similar, which reflects both that Li + is adsorbed and that adsorption is noninstantaneous (otherwise the Li + peak arrival would have been retarded).…”
Section: Resultssupporting
confidence: 62%
“…Lower ε 15 N-NH 4 + (in absolute values) could be explained by some potential contribution of plant assimilation in the systems. Hellman et al (2022) suggested that the mixed vegetation at the infiltration area contributed to the NH 4 + attenuation in the SAT-PRB system at the beginning of the experiment. The assimilation of N-NH 4 + by different plant species reported by Emmerton et al (2001), estimated an increase in ẟ 15 N-NH 4 + of 2‰.…”
Section: Isotopic Fractionationmentioning
confidence: 98%
“…where Fidel et al, 2018;Wang et al, 2015) or plant assimilation (Desimone and Howes, 1998;Lusby et al, 1998) or due to contemporaneous production and consumption of nitrates (coupled nitrification-denitrification reaction) (Kim et al, 1997;Lusby et al, 1998; or Anammox reactions (Burgin and Hamilton, 2007;Castro-barros et al, 2017). In fact, genetic analyses of the microbial communities present in the barriers demonstrate a potential for all these microbially mediated processes to occur (Hellman et al, 2022).…”
Section: Microbial Oxidation Of Nhmentioning
confidence: 99%
“…Frequent OTUs were found separately for water and woodchips samples as described in Hellman et al (2022) and Saghaï et al (2021), resulting in 755 and 1608 core OTUs in the woodchips and water samples, respectively that retained 88.2% and 93.3% from the total OTU abundances in respective datasets. Phylogenetic diversity (Faith, 1992) of the communities was estimated using estimate_pd function in "btools" package.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The 16S rRNA sequences were processed as described in Hellman et al (2022), except that the non-redundant reference database SILVA version 138 was used to classify representative OTUs. SINA (Pruesse et al, 2012) was used to align nucleotide sequences of the representative OTUs to the SILVA database, and FastTree (Price et al, 2009) with the Jukes-Cantor and CAT model (Jukes and Cantor, 1969) was used to construct a phylogenetic tree from the aligned sequences.…”
Section: Sequencing and Bioinformatic Analyses Of 16s Rrna Genesmentioning
confidence: 99%